Development of Flipbook-Based Digital Teaching Media to Increase Student Learning Interest in Science Material - Nurul Aflah; Sujarwo (Journal of Practice Learning and Educational Development, 2026)
In this research and development aims to produce a product in the form of digital teaching media based on Flipbook on the subject of Science and Natural Sciences, the product developed is then tested for its feasibility by experts and gets responses from teachers and students. The design used by researchers to develop digital teaching media based on Flipbook is a design with the ADDIE development model. This research was applied to fourth grade students on the material "Indonesiaku Kaya Budaya" which took place at SDS Islam Ash-Sholihah. Researchers chose this subject because of the low interest in learning students and the lack of teachers who use learning media in the teaching and learning process. The types of data collected in this study were in the form of observation results, questionnaires (questionnaires), and documentation. Measuring instruments in research are usually called research instruments. The instrument in this study is an instrument to measure the validity of learning media using a questionnaire with a checklist format with several statements. This questionnaire was given to several media experts and material experts. After the research data was obtained through the questionnaire, data analysis was carried out in the form of N-gain. Based on the results of the research and data analysis that have been carried out, it can be concluded that the development of digital teaching media based on flipbooks has a positive impact on increasing the interest in learning fourth grade students on the subject of Science and Natural Sciences, especially "Indonesiaku Kaya Budaya". This is indicated by the increase in the average value from pretest to posttest, as well as the N-Gain value which is included in the high category for both students (0.7) and teachers (0.8). The use of flipbooks that present material visually, interactively, and interestingly has been proven to be able to increase student involvement and enthusiasm in participating in learning on the science material.